2020
DOI: 10.1016/j.expneurol.2020.113175
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-like behavior induced by salicylate depends on age and can be prevented by a single dose of 5-MeO-DMT

Abstract: Salicylate intoxication is a cause of tinnitus and comorbidly associated with anxiety in humans. In a previous work, we showed that salicylate induces anxiety-like behavior and hippocampal type 2 theta oscillations (theta2) in mice. Here we investigate if the anxiogenic effect of salicylate is dependent on age and previous tinnitus experience. We also tested whether a single dose of DMT can prevent this effect. Using microwire electrode arrays, we recorded local field potential in young (4-5-month-old) and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Interestingly, the lack of distinct sag, ADP and AHP for type B PCs does not appear related to the age/resting potential. Hence, noise trauma experiments in C57 mice should fall within an age window in which cells are mature but before the early onset of age related hearing loss (Winne et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the lack of distinct sag, ADP and AHP for type B PCs does not appear related to the age/resting potential. Hence, noise trauma experiments in C57 mice should fall within an age window in which cells are mature but before the early onset of age related hearing loss (Winne et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, both human and animal studies have shown tinnitus without hearing loss (Langers et al, 2012;Longenecker and Galazyuk, 2016), but few studies separate the two conditions. We have used a tinnitus triggering noise that does not significantly change hearing thresholds (Winne et al, 2020) to show that PCs in the auditory cortex alter their input/output function. Our results further demonstrate that in the absence of underlying cochlear pathology, plastic alterations in higher auditory areas could sustain tinnitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were acclimatized and habituated to the test equipment before subjected to GPIAS (Figure 1A) testing the capability of detecting a short (40ms) silence in background noise (60dBSPL) 100ms prior to a loud startle pulse (105dBSPL, 50ms duration), thereby suppressing the acoustic startle reflex by at least 30% (Li et al, 2013 1A) for adequate hM4Di expression in CaMKIIα expressing cells, comprising both excitatory and some inhibitory cell populations (Malfatti et al, 2021). Hearing threshold was evaluated by recording auditory brainstem responses (ABRs, Figure 1B-C) three days prior to noise exposure (1h, 90dBSPL, 9-11kHz filtered uniform white noise, followed by 2h in silence) under anesthesia in order to induce tinnitus-like behavior (Winne et al, 2020).…”
Section: Inhibition Of Camkiiα-hm4di Positive Dcn Cells Decreases Tinnitus Perceptionmentioning
confidence: 99%